Development of Mn-Zn power ferrite with low losses over a broad temperature range for applications in the high frequency region of 0.5-3 MHz. Issue 15 (1st August 2021) - Wang, Nengchao; Ying, Yao; Zheng, Jingwu; Li, Wangchang; Qiao, Liang; Cai, Wei; Li, Juan; Che, Shenglei
Abstract: Due to the rapid development of electronic devices towards high frequency, miniaturization, and high efficiency, it is imperative to develop MHz-frequency power ferrites exhibiting low loss over a broad temperature range. In this work, the broad-temperature low-loss Mn-Zn power ferrites operating in the frequency range of 0.5-3 MHz have been fabricated following the traditional oxide ceramic process. Co3 O4 was added and its content was optimized to achieve the broad-temperature characteristics of power loss. The optimal Co3 O4 content was determined to be 0.35 wt%. The power losses of this material are less than 30, 120, and 30 kW/m 3 in the broad temperature range from 0 to 120 °C under the conditions of 500kHz/50 mT, 1MHz/50 mT, and 3MHz/10 mT, respectively. This material is an ideal material for applications in power conversion electronics at high frequencies (0.5-3 MHz). The effect of Co3 O4 addition on power loss is discussed based on the compensation model of magnetocrystalline anisotropy constant. Analysis of the three parts of power loss reveals that the residual loss gradually becomes to be predominant above 1.2 MHz. The addition of Co3 O4 reduces the residual loss and increases the cut-off frequency. This is ascribed to the induced uniaxial anisotropy of Co 2+ .